2008
DOI: 10.1007/s10658-008-9344-8
|View full text |Cite
|
Sign up to set email alerts
|

Tomato chlorotic dwarf viroid in the ornamental plant Vinca minor and its transmission through tomato seed

Abstract: Two novel aspects of Tomato chlorotic dwarf viroid (TCDVd) are reported, namely that TCDVd was detected in symptomless plants of Vinca minor, a trailing ground cover surviving at subzero temperatures (−12°C); and that TCDVd was seedborne in tomato and detected in high percentages in tomato seeds and seedlings. Soaking seeds in a low concentration of sodium hypochlorite did not eliminate the viroid. The sequence analysis showed that the TCDVd isolate consists of 360 nucleotides and has sequence identity between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…Inoculation at 15°C was unsuccessful for potatoes. Although Singh and Dilworth (2009) had shown that TCDVd survived temperatures of −12°C in Vinca minor, our results indicate that 15°C may be too low for adequate replication of the viroid, thereby substantially reducing the chance of successful inoculation. This might explain both the lack of transmission during previous field experiments ( Verhoeven et al 2004) and the fact that outbreaks of PSTVd have not been observed in potatoes in the Netherlands.…”
contrasting
confidence: 56%
“…Inoculation at 15°C was unsuccessful for potatoes. Although Singh and Dilworth (2009) had shown that TCDVd survived temperatures of −12°C in Vinca minor, our results indicate that 15°C may be too low for adequate replication of the viroid, thereby substantially reducing the chance of successful inoculation. This might explain both the lack of transmission during previous field experiments ( Verhoeven et al 2004) and the fact that outbreaks of PSTVd have not been observed in potatoes in the Netherlands.…”
contrasting
confidence: 56%
“…TCDVd was found several times in Vinca sp., as reported by Singh and Dilworth (2009) before, often occurring in mixed infections with CSVd. Also the presence of CLVd is presumed in this crop, although the identification could not be completed because of low concentrations and coinfections with CSVd and TCDVd.…”
supporting
confidence: 67%
“…(D) Fruit from viroid-infected woody hosts like apple or plum may exhibit abnormal pigmentation (i.e., "color break"). However, there are other cases in which viroid infection has spread into crop species from wild or ornamental species (Navarro et al, 2009;Singh and Dilworth, 2009). (F) Infection of peach by certain variants of PLMVd leads to extreme chlorosis and loss of chlorophyll from large portions of the leaves.…”
Section: Figure 51 Symptoms Associated With Viroid Infection (A and C)mentioning
confidence: 99%